Archival Documents in the Reconstruction of the History of Academic Pedagogy of XIX – the Beginning of XX Centuries - Kuzmina, Svitlana (Pedagogical Discourse, 2013)
The paper analyzes the cognitive possibilities of culturological approach in the study of the history of academic pedagogy in Ukraine. The typology of archival documents as sources of the reconstruction of the standards of teaching pedagogy in Kiev higher institutions of XIX – the beginning of XX centuries which was developed on the ground of this approach is presented.